American Politics in the Age of Ignorance: Why Lawmakers Choose Belief over Research - Schultz, D.; SpringerLink (Online service) (New York : Palgrave Macmillan US : Imprint: Palgrave Pivot, 2013)
American Politics in the Age of Ignoranc e looks at ten policy myths and bad ideas that governments and public officials - most often conservatives - consistently repeat and re-enact. Acting on these myths, the policies inevitably fail and thereby reinforce preconceived beliefs that government is ineffective at solving problems.
Keywords: Europe—Politics and government; Political science; Public policy; Social policy; United States—Politics and government; European Politics; Political Science; Public Policy; Social Policy; US Politics